Pengaruh Parkir Di Badan Jalan Terhadap Biaya Operasional Kendaraan dan Biaya Kemacetan di Jalan Perkotaan Mojokerto - Mutiara Firadusi; Adisura Maskur; Nafila El Hafizah; Kurnia Hadi Putra (Institut Teknologi Adhi Tama Surabaya, 2022)
Traffic congestion is a problem in big cities in Indonesia, congestion is also one of the factors causing the increase in vehicle operating costs that are detrimental to vehicle owners. The growth of vehicles which has increased every year is also a cause of congestion if it is not followed by road developments. Mojokerto City is a city that has a fairly large population, the population of Mojokerto City is based on the projected population of Indonesia 2010-2035, which is 143,377 people in 2018 and the population growth rate per year 2017-2018 is 0.33% (BPS, 2019). Due to the congestion caused by parking on the road, it will affect vehicle operating costs. Vehicle operating costs include any costs incurred by the driver to operate a vehicle. From the results of the survey conducted, it is known that the difference between the cost of congestion and the maximum parking levy on weekdays is Rp. 17,504,087.40, - and an average of Rp. 1,750,408.74,-, while on weekends it is Rp. 77,977,312.84,- for the maximum and Rp.7,797,731.28,-. It is expected to be able to analyze vehicle operational costs, parking retribution costs and congestion costs when crossing the road and can provide suggestions to increase parking space for vehicles on Jalan Benteng Pancasila, Mojokerto City.